Intracerebral Hemorrhage of Brainstem in triple pregnancy after in vitro fertilization by receiving Ovum Donation: A case report and review - Winarno, Andreas Suhartoyo; Schloesser, Lukas; Dietzel, Frederic; Balan, Percy; Hoehn, Thomas; Hampl, Monika; Fehm, Tanja Natascha (Clinical Journal of Obstetrics and Gynecology, 2019)
Deliveries prior to 28 weeks’ gestation (extreme preterm birth) pose a global health concern, according to the World Health Organization (WHO). Extreme preterm birth is associated with several complications in the newborn and management in neonatal intensive care unit would incur high expenses. In parallel, advancements in in vitro fertilization will give an opportunity for women to conceive in cases of ovarian failure. At the same time, health providers also encourage patients to receive more than one embryo simultaneously during an embryo transfer. Here we report a case of a patient in coma condition of triplet pregnancy, post ovum donation with three-embryo transfer. Following stabilization, cranial computed tomography (CCT) was performed. The result showed bleeding in the brainstem and into intraventricular spaces at 25+4 gestation weeks. Furthermore, ICH during pregnancy is considered as a rare case in obstetrical field, especially involving the brainstem. This could lead to life-threatening conditions and serious disability in the future. On the fifth day of hospitalization, she suffered from pneumonia and pulmonary edema. On the eight day (26+5 gestations weeks), an emergency caesarean section was performed due to fully dilated of the cervix with breech presentation of all fetuses. Mother and the children survived with some non-life-threatening disabilities. This is the very first case reported of intracerebral hemorrhage in the brainstem in triplet pregnancy after receiving ovum donation. Heterologous conception could be an iceberg phenomenon of gestational complications among the population. Reproductive tourism could still become greater in the future.